URGENSI MENGHINDARI PERILAKU CHEATING DALAM PERSPEKTIF HADIS - Vivin Devi Prahesti; Novita Istiqomah; Jumadil Akhir; Zulkipli Lessy (INOPENDAS: Jurnal Ilmiah Kependidikan, 2022)
The research aims that to determine the imprortant to avoid cheatingbased on Hadis perspektif being happened in students. The one uselibrary research and managing the data is by kualitative approachment.The source of data gains from book and journal sources being relevantwith the research. The data is collected by documentation in somesources. The data is analyzed by descriptive analizing, and the researchfinding states that avoiding cheating is important to the students toreduce bad thing in the future, so that students have to consider about theaction one giving an impact to their life based on hadis perspektif. Byresearch about the important avoid cheating based on hadis perspektifthat students can determine the bad and the good thing to imitate othersin order to reduce learning problem.